Conducting multinational, cross‐cultural research in the functional gastrointestinal disorders: issues and recommendations. A Rome Foundation working team report. Issue 9 (1st September 2014) - Sperber, A. D.; Gwee, K. A.; Hungin, A. P.; Corazziari, E.; Fukudo, S.; Gerson, C.; Ghoshal, U. C.; Kang, J.‐Y.; Levy, R. L.; Schmulson, M.; Dumitrascu, D.; Gerson, M.‐J.; et al.
Summary Background Cross‐cultural, multinational research can advance the field of functional gastrointestinal disorders (FGIDs). Cross‐cultural comparative research can make a significant contribution in areas such as epidemiology, genetics, psychosocial modulators, symptom reporting and interpretation, extra‐intestinal co‐morbidity, diagnosis and treatment, determinants of disease severity, health care utilisation, and health‐related quality of life, all issues that can be affected by geographical region, culture, ethnicity and race. Aims To identify methodological challenges for cross‐cultural, multinational research, and suggest possible solutions. Methods This report, which summarises the full report of a working team established by the Rome Foundation that is available on the Internet, reflects an effort by an international committee of FGID clinicians and researchers. It is based on comprehensive literature reviews and expert opinion. Results Cross‐cultural, multinational research is important and feasible, but has barriers to successful implementation. This report contains recommendations for future research relating to study design, subject recruitment, availability of appropriate study instruments, translation and validation of study instruments, documenting confounders, statistical analyses and reporting of results. Conclusions Advances in study design and methodology, as well as cross‐cultural research competence, have not matched technological advancements. The development of multinational research networks and cross‐cultural research collaboration is still in its early stages. This report is intended to be aspirational rather than prescriptive, so we present recommendations, not guidelines. We aim to raise awareness of these issues and to pose higher standards, but not to discourage investigators from doing what is feasible in any particular setting.